God and the New Physics - Davies, Paul, 1946- (London : Penguin books, 1990)
Science and religion in a changing world; genesis; did God create the universe?; what is life? - Holism vs reductionism; mind and soul; the self; the quantum factor; time; free will and determinism; the fundamental structure of matter; accident or design?; black holes and cosmic chaos; miracles; the end of the universe; is the universe a "free lunch"?; the physicist's conception of nature.
Explains how the far-reaching discoveries of physics are revolutionizing our world and, in particular, throwing light on many of the questions formerly posed by religion, such as: Why is there a universe? Where did we come from? What is life? How is the world organized?